PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA DIMEDIASI MOTIVASI GURU MTS SWASTA DI KKMTs N MARGOYOSO - Santosa, Teguh (Students Journal of Economic and Management, 2012)
This research aims to analyze the influence on competence as will as work satisfactionto ward the work performence mediated by motivation (a research on teachers in the religion of KKMTs Margoyoso within the eks- Tayu sub distric-PatiÂ regency).The research is qualitative one in wich a proportional random sampling is imployed. Population of this research causistsof 316 teachers who work in private Islamic Junior High Schools in the religion of KKMTs N Margoyoso. Either formula âslovinâ and technique of the proportional random sampling are implemented to sum of 177 respondens, measurement of the research uses o close questionnaire from wich the â likert scaleâ with 7 alternative items for respondens to answer is employed. The result of the research shows that coefficient of determination I (Adjusted R Square) is o,616. This means that variabel of motivation can be explained by the variable of competence, work satisfaction earns a sum of 61,6%.White the rest numberor 39,4% is explained by other variable. The coefficient of determination II(Adjusted of Square) is 0.508. This means that the variable of work performancecan be explained by variables of competence and satisfaction work. White motivation earns a sum of 50,8% and a number of 49,5% as the rest number is explained by other variable which is not included in this research.Being implemented t- test, the result of sig t-0 variable is below 0,05 and 0 is above 0.05. Key word :competence,satisfaction work, motivation, and work performance.